Ruang Sehati: Innovating Portable Lactation Pods for Wellness Tourism Using Design Thinking Method in Yogyakarta - Okinarum, Giyawati Yulilania; Vidayanti, Venny; Mulyani, Sri Hasta (Universitas Islam Bandung, 2024)
Yogyakarta, a renowned tourist city in Indonesia, currently needs more lactation rooms and public facilities within tourist areas. To address this, inventors propose a portable lactation pod. This study utilized the design thinking method, emphasizing user needs. Interviews were conducted with thirty breastfeeding mothers on Malioboro Street in Yogyakarta to assess the necessity of lactation rooms in this popular tourist spot. From February to June 2022, the stages of